Organizational and legal basis for the professional activity of the psychological service - D. E. Udalov; E. A. Kovtun (Путеводитель предпринимателя, 2020)
The article examines the main principles that determine the order of the psychologist’s activity in the organization. The professional activity of a psychologist is characterized by the concept of an activity approach. The content of the basic normative legal acts that establish the rights and duties of a psychologist is analyzed. The subject of the study are the social relations that arise in the process of organizing the professional activity of a psychologist. Methods of carrying out the work. During the research, the main sources of input data were legislative and regulatory acts, fundamental and applied works ofauthoritative scientists in the field of research. The research is based on theoretical methods of scientific knowledge, in particular, the use of methods of synthesis and deduction, as well as methods of empirical cognition. Conclusions: Based on the conducted analysis of regulatory legal acts, the article concluded that the professional activity of the organization’s psychologist is mainly regulated by the norms of labor and social legislation.